Update on the Neisseria Macrophage Infectivity Potentiator-Like PPIase Protein - Christodoulides, Myron (Frontiers in Cellular and Infection Microbiology, 2022)
Neisseria pathogens express a Macrophage Infectivity Potentiator Protein (MIP), which belongs to the FK506 binding protein (FKBP) family of proteins that exhibit peptidyl-prolyl cis/trans isomerase (PPIase) activity. Neisseria MIP proteins are potential candidates for inclusion into vaccines for gonorrhoea caused by N. gonorrhoeae infection, and meningitis/sepsis caused by M. meningitidis infection. Neisseria MIP proteins are also potential targets for directed drug treatments, although this remains relatively unexplored. In this mini-review, we provide an update into the vaccine potential of Neisseria MIP and the few published drug targeting studies, and explore further the diversity of this protein amongst both pathogenic and commensal Neisseria spp.